Electrode preparation method of aqueous lithium ion battery, electrode and battery
By using iron phosphate as the negative electrode material in water-based lithium-ion batteries and adopting specific preparation methods, the problem of poor stability of the negative electrode material is solved, the stability performance and safety of the battery are improved, and the market's high-performance and environmentally friendly batteries are met. need.
Patent Information
- Application Number
- CN202411630707.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
The negative electrode material of existing water system lithium-ion batteries has poor stability, resulting in a low operating voltage, low energy density and poor cycle stability.
Iron phosphate is used as the negative electrode material for aqueous lithium-ion batteries, and electrode sheets are prepared by mixing different crystalline iron phosphate with conductive agent and binder, and then grinding them evenly, coating them on a current collector and heating and drying.
It significantly improves the overall stability of the battery, improves the safety and environmental friendliness of the battery, and reduces the manufacturing cost of the battery, meeting the market's demand for high-performance and environmentally friendly battery technology.
Smart Images

Figure CN119447153A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing an aqueous lithium ion battery electrode, the prepared electrode and a battery comprising the electrode. Background Art
[0002] With the increasing consumption of fossil energy and the increasing environmental pollution, researchers have gradually begun to pay attention to renewable energy, such as wind energy, solar energy and geothermal energy. However, renewable energy is often difficult to be effectively utilized due to environmental problems, high operating costs and the need for large areas of land. Therefore, it is particularly important to develop efficient energy storage technology. Among various electrochemical energy storage devices, lithium-ion batteries have become the focus of research in energy storage technology due to their strong charge retention ability, long cycle life, fast charging speed and strong environmental adaptability. Since their commercialization, lithium-ion batteries have been widely used in energy storage, electric bicycles, special aerospace and medical equipment. Traditional lithium-ion batteries mainly use organic carbonate electrolytes because they are well compatible with lithium cobalt oxide or ternary positive electrode and graphite negative electrode materials, and can withstand the high voltage of lithium cobalt oxide / graphite system lithium-ion batteries. Compared with organic electrolytes (mainly carbonate electrolytes), aqueous electrolytes have the advantages of being non-toxic, non-flammable, low cost and low requirements for the production environment. At the same time, in aqueous electrolytes, the ionic conductivity is several orders of magnitude higher than that in organic electrolytes, which greatly improves the rate and fast charging performance of lithium-ion batteries.
[0003] Aqueous lithium-ion batteries are battery systems based on aqueous solutions. It is difficult to achieve the conditions required for combustion, and the aqueous electrolyte is generally neutral, which can avoid the hazards caused by the excessive acidity and alkalinity of traditional lead-acid batteries and nickel-metal hydride batteries. It has the advantages of high safety, environmental friendliness, and low cost, and is very suitable for the large-scale energy storage market. However, due to the narrow electrochemical stability window of aqueous electrolytes, hydrogen and oxygen evolution reactions are very likely to occur, and are also accompanied by the dissolution of electrode materials and the instability of the electrode material structure during charging and discharging. Therefore, the operating voltage of aqueous batteries is low, the energy density is low, and the cycle stability is poor. Therefore, optimizing the electrolyte composition, widening the electrolyte electrochemical window, and selecting suitable positive and negative electrode materials are the key to developing high energy density and long life aqueous batteries.
[0004] Iron phosphate has excellent chemical stability and structural stability, and is abundant in resources, low in price, and environmentally friendly. Therefore, developing iron phosphate as a new negative electrode material for aqueous lithium-ion batteries can not only improve the safety and environmental friendliness of the battery, but also significantly reduce the manufacturing cost of the battery and improve the overall stability of the battery. It is a highly potential negative electrode material that will help promote the development and application of aqueous lithium-ion battery technology. Summary of the invention
[0005] The present invention aims to provide an aqueous lithium-ion battery using iron phosphate as a negative electrode material and a preparation method thereof, so as to solve the problem of poor stability of negative electrode materials in the prior art and improve the overall stability of the battery. By selecting iron phosphate as the negative electrode material, the present invention can effectively improve the safety and environmental friendliness of the battery, while reducing the manufacturing cost of the battery, and meet the market demand for high-performance, environmentally friendly battery technology.
[0006] In order to achieve the above object, the technical solution of the present invention is as follows: A method for preparing an electrode of an aqueous lithium-ion battery comprises the following steps:
[0007] (1) Iron phosphates of different crystal forms, a conductive agent and a binder are mixed and ground evenly.
[0008] (2) The ground material obtained in step (1) is coated on a current collector, and then heated and dried to obtain an electrode sheet.
[0009] Preferably, the iron phosphate of different crystal forms includes one or more of monoclinic, hexagonal, trigonal, amorphous, and orthorhombic.
[0010] Preferably, the conductive agent is selected from at least one of activated carbon, superconducting carbon black, carbon fiber, foamed carbon, acetylene black, mesoporous carbon, carbon nanotubes, graphite and graphene; in a specific embodiment, the conductive agent is selected from at least one of superconducting carbon black, acetylene black, graphite and foamed carbon;
[0011] Preferably, the binder is selected from at least one of polyethylene oxide, polypropylene oxide, polyacrylonitrile, polyimide, polyester, polytetrafluoroethylene, fluorinated polymer, polydivinyl polyol, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate;
[0012] Preferably, the current collector in the above step (2) is: stainless steel foil, copper foil, titanium foil, aluminum foil, nickel foil or porous metal material, such as stainless steel mesh, foam copper, foam nickel, carbon cloth.
[0013] In step (1) of the above scheme, the total mass of iron phosphate, conductive agent and binder is 100%, wherein the mass fraction of iron phosphate is 20-95%, the mass fraction of conductive agent is 2-50% and the mass fraction of binder is 1-35%.
[0014] The drying temperature in the above step (2) is 50-200° C. and the drying time is 2-18 hours.
[0015] One of the objectives of the present invention is to provide an electrode sheet prepared by the above-mentioned electrode preparation method.
[0016] A second object of the present invention is to provide an aqueous lithium-ion battery having a negative electrode sheet formed by the above-mentioned electrode sheet.
[0017] In order to achieve the above-mentioned purpose, the technical solution of the present invention is as follows: a battery comprises a negative electrode sheet, a separator, an electrolyte and a positive electrode sheet, wherein the negative electrode sheet and the positive electrode sheet are separated by a separator with an electrolyte.
[0018] The negative electrode sheet in the above solution is composed of the electrode sheet described above.
[0019] The membrane described in the above scheme is a polyethylene membrane, a polypropylene membrane, a glass fiber filter paper, a Nafion membrane, a qualitative filter paper, a polyimide membrane, a polyacrylonitrile membrane, a meta-aramid membrane, and a composite membrane thereof.
[0020] The electrolyte described in the above scheme is an aqueous solution containing a lithium salt, and the lithium salt is at least one of lithium perchlorate, lithium nitrate, lithium sulfate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(oxalate borate), lithium difluorooxalate borate, lithium bis(trifluoromethylsulfonyl imide), and lithium bis(pentafluoroethylsulfonyl imide).
[0021] In the above scheme, the positive electrode is lithium cobalt oxide, lithium manganese oxide, lithium vanadium phosphate, spinel nickel lithium manganese oxide or Prussian blue.
[0022] The battery negative electrode sheet described in the above scheme is an aqueous lithium-ion battery negative electrode material.
[0023] Compared with the existing inventions, the present invention has the following beneficial effects:
[0024] (1) Develop a new negative electrode material to open up new possibilities for the development of aqueous lithium-ion batteries.
[0025] (2) Iron phosphate raw materials are abundant, low-priced, and widely available, which helps reduce the manufacturing cost of batteries and can meet market needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the constant current charge and discharge curve of the monoclinic iron phosphate negative electrode material in Example 1.
[0027] Figure 2 The discharge specific capacity-cycle number of the monoclinic iron phosphate negative electrode material in Example 1. DETAILED DESCRIPTION
[0028] The present invention is described in detail below in conjunction with the examples, but the present invention is not limited to these examples. Unless otherwise specified, the raw materials in the examples of the present invention are purchased through commercial channels. The analysis method in the examples of the present invention is as follows: The electrochemical performance test of the battery is carried out using the BTS-5V20mA battery testing equipment of Shenzhen Xinwei Electronics Co., Ltd. to perform electrical performance analysis.
[0029] Example 1: Preparation of monoclinic iron phosphate negative electrode material and battery assembly
[0030] (1) Preparation of negative electrode material: Grind 70% monoclinic iron phosphate and 20% superconducting carbon black (Super P) in an agate mortar for 30 minutes. After confirming that the grinding is uniform, add 10% polyvinylidene fluoride (PVDF) binder and grind into slurry. Then, add N-methylpyrrolidone (NMP) as a solvent to the mixture to obtain a viscous slurry. The slurry is evenly coated on a graphite foil current collector with a coating thickness of 200 μm, and dried at 60°C for 6 hours to remove the NMP solvent to obtain a negative electrode sheet.
[0031] (2) Preparation of positive electrode materials: Commercially available LiCoO2 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0032] (3) Battery assembly: The positive electrode, separator and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case, 2M lithium nitrate aqueous solution is injected as the electrolyte, glass fiber is used as the separator, and finally the battery case is sealed.
[0033] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 0.2mA / g, with a test voltage range of 0 to 1.8V, and a cycle stability test of 500 cycles was performed, recording the charge and discharge capacity and voltage platform of each cycle. The test results showed that the battery had a maximum discharge capacity of 95mAh / g, but it decayed rapidly. Figure 1 The constant current charge and discharge curve of the battery, the discharge specific capacity-cycle number curve is as follows Figure 2 As shown. After testing, the maximum discharge capacity of the assembled battery is 95mAh / g, and the discharge capacity rapidly decays after reaching the maximum value.
[0034] Example 2: Preparation of hexagonal iron phosphate negative electrode material and battery assembly
[0035] (1) Preparation of negative electrode material: Using the same method as in Example 1, 80% hexagonal iron phosphate and 10% superconducting carbon black (Super P) were ground in an agate mortar for 30 minutes. After confirming that the grinding was uniform, 10% polyvinylidene fluoride (PVDF) binder was added and ground into slurry. Then, N-methylpyrrolidone (NMP) was added to the mixture as a solvent to obtain a viscous slurry. The slurry was evenly coated on a graphite foil current collector, the coating thickness was controlled to be 200 μm, and dried at 60°C for 6 hours to remove the NMP solvent to obtain a negative electrode sheet.
[0036] (2) Preparation of positive electrode material: Commercially available LiMn2O4 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0037] (3) Battery assembly: The positive electrode, separator, and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case. A 2M lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) aqueous solution is injected as the electrolyte. Glass fiber is used as the separator. Finally, the battery case is sealed.
[0038] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 0.2 mA / g, with a test voltage range of 0 to 1.8 V, and the cycle stability was tested for 500 cycles.
[0039] Example 3: Preparation of trigonal iron phosphate negative electrode material and battery assembly
[0040] (1) Preparation of negative electrode material: Using the same method as in Example 1, 80% trigonal iron phosphate and 10% superconducting carbon black (Super P) were ground in an agate mortar for 35 minutes. After confirming that the grinding was uniform, 10% polyvinylidene fluoride (PVDF) binder was added to grind into slurry. Then, N-methylpyrrolidone (NMP) was added to the mixture as a solvent to obtain a viscous slurry. The slurry was evenly coated on a graphite foil current collector, the coating thickness was controlled to be 150 μm, and dried at 60°C for 6 hours to remove the NMP solvent to obtain a negative electrode sheet.
[0041] (2) Preparation of positive electrode materials: Commercially available LiCoO2 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0042] (3) Battery assembly: The positive electrode, separator, and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case. A 2M lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) aqueous solution is injected as the electrolyte. Glass fiber is used as the separator. Finally, the battery case is sealed.
[0043] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 2 mA / g, with a test voltage range of 0 to 1.8 V, and the cycle stability was tested for 550 cycles.
[0044] Example 4: Preparation of amorphous iron phosphate negative electrode material and battery assembly
[0045] (1) Preparation of negative electrode material: Grind 70% amorphous iron phosphate and 20% superconducting carbon black (Super P) in an agate mortar for 30 minutes. After confirming that the grinding is uniform, add 10% polyvinylidene fluoride (PVDF) binder and grind into slurry. Then, add N-methylpyrrolidone (NMP) as a solvent to the mixture to obtain a viscous slurry. The slurry is evenly coated on a graphite foil current collector with a coating thickness of 200 μm, and dried at 60°C for 6 hours to remove the NMP solvent to obtain a negative electrode sheet.
[0046] (2) Preparation of positive electrode materials: Commercially available LiCoO2 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0047] (3) Battery assembly: The positive electrode, separator and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case, 2M lithium nitrate aqueous solution is injected as the electrolyte, glass fiber is used as the separator, and finally the battery case is sealed.
[0048] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 0.2 mA / g, with a test voltage range of 0 to 1.6 V. A cycle stability test was performed for 500 cycles, and the charge and discharge capacity and voltage platform of each cycle were recorded.
[0049] Example 5: Preparation of monoclinic, hexagonal, and trigonal mixed crystal iron phosphate negative electrode materials and battery assembly
[0050] (1) Preparation of negative electrode material: Using the same method as in Example 1, 60% by mass of monoclinic, hexagonal, and trigonal mixed iron phosphate (1:1:1 ratio) and 30% superconducting carbon black (Super P) were ground in an agate mortar for 35 minutes. After confirming that the grinding was uniform, 10% of polyvinylidene fluoride (PVDF) binder was added to grind into slurry. Then, N-methylpyrrolidone (NMP) was added to the mixture as a solvent to obtain a viscous slurry. The slurry was evenly coated on a graphite foil current collector, the coating thickness was controlled to be 200 μm, and dried at 60°C for 6 hours to remove the NMP solvent to obtain a negative electrode sheet.
[0051] (2) Preparation of positive electrode materials: Commercially available LiCoO2 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0052] (3) Battery assembly: The positive electrode, separator, and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case. A 1 M lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) aqueous solution is injected as the electrolyte. Glass fiber is used as the separator. Finally, the battery case is sealed.
[0053] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 2 mA / g, with a test voltage range of 0 to 1.6 V, and the cycle stability was tested for 500 cycles.
[0054] Example 6: Preparation of monoclinic and hexagonal mixed crystal iron phosphate negative electrode materials and battery assembly
[0055] (1) Preparation of negative electrode material: Using the same method as in Example 1, 60% by mass of monoclinic and hexagonal mixed iron phosphate (1:1 ratio) and 30% superconducting carbon black (Super P) were ground in an agate mortar for 35 minutes. After confirming that the grinding was uniform, 10% of polyvinylidene fluoride (PVDF) binder was added to grind into slurry. Then, N-methylpyrrolidone (NMP) was added to the mixture as a solvent to obtain a viscous slurry. The slurry was evenly coated on a graphite foil current collector, the coating thickness was controlled to be 150 μm, and dried at 60°C for 6 hours to remove the NMP solvent to obtain a negative electrode sheet.
[0056] (2) Preparation of positive electrode materials: Commercially available LiCoO2 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0057] (3) Battery assembly: The positive electrode, separator, and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case. A 3M lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) aqueous solution is injected as the electrolyte. Glass fiber is used as the separator, and the battery case is finally sealed.
[0058] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 2 mA / g, with a test voltage range of 0 to 1.6 V, and the cycle stability was tested for 500 cycles.
[0059] Example 7: Preparation of trigonal, amorphous, orthorhombic mixed crystal iron phosphate negative electrode materials and battery assembly
[0060] (1) Preparation of negative electrode material: Using the same method as in Example 1, 80% by mass of a trigonal, amorphous, orthorhombic mixed iron phosphate (1:1:1 ratio) and 10% superconducting carbon black (Super P) were ground in an agate mortar for 40 minutes. After confirming that the grinding was uniform, 10% of polyvinylidene fluoride (PVDF) binder was added and ground into a slurry. Then, N-methylpyrrolidone (NMP) was added to the mixture as a solvent to obtain a viscous slurry. The slurry was evenly coated on a graphite foil current collector, the coating thickness was controlled to be 150 μm, and dried at 65°C for 6 hours to remove the NMP solvent to obtain a negative electrode sheet.
[0061] (2) Preparation of positive electrode materials: Commercially available LiCoO2 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0062] (3) Battery assembly: The positive electrode, separator and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case, 2M lithium nitrate aqueous solution is injected as the electrolyte, glass fiber is used as the separator, and finally the battery case is sealed.
[0063] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 2 mA / g, with a test voltage range of 0 to 1.6 V, and the cycle stability was tested for 500 cycles.
Claims
1. A method for preparing an electrode for an aqueous lithium-ion battery, characterized in that: The steps include: (1) mixing iron phosphate of different crystal forms, a conductive agent and a binder and grinding the mixture evenly; (2) Apply the slurry obtained in step (1) on the current collector and obtain an electrode sheet after drying.
2. The method for preparing an aqueous lithium-ion battery electrode according to claim 1, characterized in that: The different crystal forms of the iron phosphate in step (1) include one or more of monoclinic, hexagonal, trigonal, amorphous, and orthorhombic.
3. The method for preparing an electrode for an aqueous lithium-ion battery according to claim 1, characterized in that: The conductive agent described in step (1) is selected from at least one of activated carbon, superconducting carbon black, carbon fiber powder, foamed carbon, acetylene black, mesoporous carbon, carbon nanotubes, graphite and graphene; in a specific embodiment, the conductive agent is selected from at least one of superconducting carbon black, acetylene black, graphite and foamed carbon.
4. The method for preparing an aqueous lithium-ion battery electrode according to claim 1, characterized in that: The binder described in step (1) is selected from at least one of polyethylene oxide, polypropylene oxide, polyacrylonitrile, polyimide, polyester, polytetrafluoroethylene, fluorinated polymer, polydivinyl polyol, polyethylene glycol diacrylate, and polyethylene glycol dimethacrylate.
5. The method for preparing an aqueous lithium-ion battery electrode according to claim 1, characterized in that: The current collector described in step (2) is stainless steel foil, copper foil, titanium foil, aluminum foil, nickel foil or porous metal material, such as stainless steel mesh, foam copper, foam nickel, carbon cloth.
6. The method for preparing an electrode for an aqueous lithium-ion battery according to claim 1, characterized in that: The total mass of the iron phosphate, the conductive agent and the binder in step (1) is 100%, wherein the mass fraction of the iron phosphate is 20-95%, the mass fraction of the conductive agent is 2-50%, and the mass fraction of the binder is 1-35%.
7. An aqueous lithium-ion battery, comprising a negative electrode sheet, a separator, an electrolyte and a positive electrode sheet, wherein the negative electrode sheet and the positive electrode sheet are inserted on both sides of the separator with the electrolyte, characterized in that: The negative electrode sheet is composed of the electrode sheet made according to claims 1-6.
8. The battery according to claim 7, characterized in that The diaphragm is a polyethylene diaphragm, a polypropylene diaphragm, a glass fiber filter paper, a Nafion membrane, a qualitative filter paper, a polyimide diaphragm, a polyacrylonitrile diaphragm, a meta-aramid diaphragm, and a composite membrane thereof.
9. The battery according to claim 8, characterized in that The electrolyte is an aqueous solution containing a lithium salt, the concentration of the electrolyte in the electrolyte is 0.5M to 5M, and the selected lithium salt is at least one of lithium perchlorate, lithium nitrate, lithium sulfate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium bis(oxalate borate), lithium difluorooxalate borate, lithium bis(trifluoromethylsulfonyl imide), and lithium bis(pentafluoroethylsulfonyl imide).
10. The battery according to claim 7, characterized in that The positive electrode is lithium cobalt oxide, lithium manganese oxide, lithium vanadium phosphate, spinel nickel lithium manganese oxide or Prussian blue.